Fatigue crack growth of composite patch repaired Al-alloy plates under variable amplitude loading (Fracture and Structural Integrity, 2017)
In this paper, fatigue crack growth of edge crack in 2024 T351 aluminum alloy plate repaired with bonded composite patch under constant and variable amplitude loading (VAL) was predicted. The Al-alloy plate was repaired with symmetric patch “Boron/Epoxy”. Additionally to constant amplitude loading (CAL), the effects of single overload and band overload were investigated for repaired and unrepaired Al-alloy plates. The obtained results confirm the improvement in repair performances by composite patch on fatigue lives and crack growth rates for all applied cycles (CAL and VAL) compared to unrepaired plates. A retardation effect was observed in application of single overload compared to band overload with the same stress ratio (R=0.2) for unpatched plate and characterized by instantaneous delays. However, this retardation effect is increased by the presence of the patch repair which leads to the higher fatigue life. Retardation effect was neglected for lower overload ratio (ORL>1.8). Comparison in fatigue life and crack growth rates under the same overload ratio (ORL=2.4) between repaired and unrepaired plates show the supplementary beneficial effects in combination of overloading and patch repair
Keywords: Fatigue crack; Composite patch repair; Variable amplitude loading; Retardation; Al-alloy